FLUCTUATION DU TAUX D’INTERET DIRECTEUR SUR LA DEMANDE DE MONNAIE EN REPUBLIQUE DEMOCRATIQUE DU CONGO - Moustapha, GENDANU TEREMBI; NYALUSALA IKANDO Yvette ,; ANGONDO ASAKA John ,; ANIBILONI SUNGUFUE Brigitte ,; BEMBONGA MOGANGA Benjamin,; MATATA MAKALAMBA Patrick ,; BOLINGOLA BOSSESSILO Jean-Faustin , (IJRDO - Journal of Business Management, 2019)
The present survery is about the fluctuation of the leading interesr rate and the demand of currency in Democratic Republic of Congo. He/it is question to understand the impact of the fluctuations of the leading interest rate on the demand of the currency ; because the RDC is in front of the mutations, of the financial waste that hinders the good working of his/her/its institutions.The objective pursued by this survery is to analyse the effects of the fluctuations of the currency. The banks are in the center of the development of a country, from where the necessity of this survery that will help the banking authorities to really master the leading interest rate.